World Trade Under GATT and the Filipino Peasantry - Montemayor, Leonard Q. (Kasarinlan: Philippine Journal of Third World Studies, 2011)
Farmers from the Philippines were generally unaware of the progress of General Agreement on Tariffs and Trade (GATT) negotiations since the beginning of the Uruguay Round. The government failed to consult farmers regarding the country’s continuing membership to the GATT and to give farmers any notification of the results of ongoing deliberations prior to the treaty’s ratification—despite the fact that Filipino farmers are potentially the most adversely affected by the treaty’s mandates. To answer for this omission, the paper seeks to explore the impacts of the latest GATT treaty on farmers in terms of policy considerations. It criticizes the Philippine government for entering into an agreement wherein Filipino farmers are at a clear disadvantage; in contrast to government-subsidized farmers in industrialized nations, Filipino farmers have never received any substantial support from the government. Hence, the production costs of Filipino farmers are much higher than those of farmers from the developed world. Moreover, the trend in resource allocation in the Philippines has been towards industrialization rather than agricultural development, despite the latter being more in line with safeguarding the continued viability of the country’s resources. The paper argues that the “free trade” mindset, which engendered this misappropriation, treats agriculture like any other economic activity, and reduces farmers to mere producers of tradeable items. The paper furthers the argument that the Philippines should not be a party to the trade agreement by citing provision of the Philippine Constitution that seem incompatible with the GATT treaty. In sum, it states that only the multinational traders of agricultural commodities will benefit from the GATT treaty; no such benefit will inure to unsupported, unorganized farmers.
Keywords: GATT · industrialization · agricultural development · free trade · Philippines